Deuterium chemistry and D/H ratios in Class 0/I proto-brown dwarfs. Issue 4 (27th January 2022) - Riaz, B; Thi, W-F
ABSTRACT: We have conducted the first extensive observational survey of several deuterated species in 16 Class 0/I proto-brown dwarfs (proto-BDs) and 4 Class Flat/Class II brown dwarfs. Observations were obtained with the IRAM 30m telescope in the DCO + (3–2), DCN (3–2), DNC (3–2), and N2 D + (3–2) lines. The DCO + /H 13 CO +, DCN/H 13 CN, and DNC/HN 13 C ratios are comparatively higher and show a narrower range than the DCO + /HCO +, DCN/HCN, and DNC/HNC ratios, respectively. The mean D/H ratios for the proto-BDs derived from these molecules are in the range of ∼0.02–3. Both low-temperature gas-phase ion-molecule deuteron transfer and grain surface reactions are required to explain the enhanced deuterium fractionation. The very dense and cold (n_H_2 10^6 cm −3, T ≤10 K) interior of the proto-BDs provide the suitable conditions for efficient deuterium fractionation in these cores. There is no correlation between the D/H ratios and the CO depletion factor, with the exception of the DCN/HCN ratios that show a strong anti-correlation possibly due to the difference in the peak emitting regions of the DCN and HCN molecules. Over a wide range in the bolometric luminosities spanning ∼0.002–40 L⊙, we find a trend of higher DCO + /HCO + and DCN/HCN ratios, nearly constant DNC/HNC and DNC/HN 13 C ratios, and lower N2 D + /N2 H + ratios in the proto-BDs compared to protostars. Only one Class II brown dwarf shows emission in the DCO + (3–2) line. No correlation is seen between the D/H ratios and the evolutionary stage.